Lithium nickel manganese oxide positive electrode material as well as preparation method and application thereof

By doping Al, Ti, and F elements into the Ni-Manganate Lithium Manganate positive electrode material, combined with a specific preparation process, the problems of fast capacity decay and poor structural stability during the cycle are solved, and the electrochemical performance of the material is significantly improved. Cyclic stability.

CN119481033APending Publication Date: 2025-02-18HUNAN HUMP NEW ENERGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411457217.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing lithium nickel manganate positive electrode materials have problems such as fast capacity decay and poor structural stability during the circulation process, which limits their practical application.

Method used

By doping Al, Ti, F elements and combining with specific preparation processes, the microstructure of the material has excellent octahedral morphology, reducing surface position energy, and effectively controlling the proportion of ordered and disordered structures, balancing capacity and Cycle retention rate.

Benefits of technology

It significantly improves the structural stability and electrochemical performance of the material, improves the specific capacity and cycle stability of the lithium battery, and can maintain an initial capacity of more than 90% after 100 charge and discharge cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481033A_ABST
    Figure CN119481033A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium nickel manganese oxide positive electrode material as well as a preparation method and application thereof. The preparation method of the material comprises the following steps: mixing raw materials including a nickel source, a manganese source, a lithium source, an aluminum source, a titanium source and a fluorine source, performing wet grinding, drying, and performing compression molding to obtain precursor powder; and sintering and annealing the precursor powder, thereby obtaining the composite material. The lithium nickel manganese oxide positive electrode material prepared by the method has high stability and excellent electrochemical performance, and the battery capacity and the cycling stability can be remarkably improved when the lithium nickel manganese oxide positive electrode material is applied to a lithium ion battery. The preparation method is simple, low in cost and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an electrode, specifically to a lithium nickel manganese oxide cathode material, and also to its preparation method and application, belonging to the field of lithium-ion batteries. Background Technology

[0002] Lithium-ion batteries have been widely used in portable electronic devices, electric vehicles, and energy storage systems due to their high energy density, long cycle life, and environmental friendliness. Lithium nickel manganese oxide (LiNiMnO4) cathode material, with its high operating voltage and high specific capacity, has become a promising cathode material. However, existing LiNiMnO4 materials suffer from rapid capacity decay and poor structural stability during cycling, limiting their practical application. Summary of the Invention

[0003] To address the shortcomings of existing technologies, the first objective of this invention is to provide a lithium nickel manganese oxide cathode material. This electrode material exhibits high stability and excellent electrochemical performance.

[0004] The second objective of this invention is to provide a method for preparing lithium nickel manganese oxide cathode material. This method is simple, low-cost, and suitable for industrial production.

[0005] A third objective of this invention is to provide an application of a lithium nickel manganese oxide cathode material. When this electrode material is used in lithium batteries, it can significantly improve the battery's specific capacity and cycle stability.

[0006] To achieve the above-mentioned technical objectives, the present invention provides a method for preparing lithium nickel manganese oxide cathode material. The method involves mixing raw materials containing nickel source, manganese source, lithium source, aluminum source, titanium source and fluorine source, wet grinding, drying and pressing to obtain precursor powder; and then subjecting the precursor powder to sintering and annealing treatment to obtain the desired material.

[0007] This invention, through doping with Al, Ti, and F elements and combining with a specific preparation process, enables the material to exhibit an excellent truncated octahedral morphology in its microstructure, reduces surface potential energy, and effectively controls the ratio of ordered (P4332 space group) / disordered (Fd-3m) structures in the material. This balances the contradiction between the capacity and cycle retention rate of the cathode material, and significantly improves the structural stability and electrochemical performance of the material.

[0008] As a preferred embodiment, the molar ratio of lithium source, nickel source, manganese source, aluminum source, titanium source and fluorine in the raw materials is (1-1.1):(0.4-0.6):(1.4-1.6):(0.01-0.03):(0.01-0.03):(0.01-0.03), and a further preferred molar ratio of lithium source, nickel source, manganese source, aluminum source, titanium source and fluorine is (1.02-1.05):(0.49-0.51):(1.44-1.48):(0.019-0.021):(0.019-0.021):(0.019-0.021).

[0009] This invention requires controlling the raw materials of each element within a suitable range. Al and Ti are mainly used to regulate the ratio of ordered / disordered structures and to stabilize the material structure, while F mainly affects the material's capacity. Excessive Al content will affect the material's capacity, while insufficient Al content will result in minimal improvement in cycle retention. Excessive Ti content will also affect the material's capacity, while insufficient Ti content will not significantly improve the first-efficiency performance. Excessive F content will affect both the first-efficiency performance and cycle retention, while insufficient F content will not significantly improve the material's capacity.

[0010] As a preferred embodiment, the nickel source includes at least one of nickel carbonate, nickel hydroxide, nickel oxide, and nickel hydroxide.

[0011] As a preferred embodiment, the manganese source comprises manganese tetroxide and / or manganese dioxide.

[0012] As a preferred embodiment, the lithium source includes lithium carbonate and / or lithium hydroxide.

[0013] As a preferred embodiment, the aluminum source comprises aluminum oxide and / or aluminum hydroxide.

[0014] As a preferred embodiment, the titanium source is titanium dioxide.

[0015] As a preferred embodiment, the fluorine source comprises aluminum fluoride and / or lithium fluoride.

[0016] As a preferred embodiment, the solid content of the material is controlled to be 20-60 wt% during the wet milling process.

[0017] As a preferred embodiment, the drying temperature is 90–120°C, more preferably 95–110°C.

[0018] As a preferred embodiment, the pressing pressure is 10-30 MPa and the holding time is 10-20 s.

[0019] As a preferred embodiment, the sintering conditions are: an atmosphere of air and / or oxygen, a temperature of 750–950°C, and a time of 12–20 hours.

[0020] Controlling the sintering temperature and time within a suitable range is beneficial to improving material performance. Excessive sintering temperature and time can easily lead to over-burning, oxygen release from the structure, the formation of high-valence manganese, and deterioration of surface morphology, all of which affect product performance. Conversely, excessively low temperature and time result in insufficient reaction time, poor material crystallinity, and the potential formation of impurities, also negatively impacting product performance.

[0021] As a preferred embodiment, the annealing conditions are: an atmosphere of air and / or oxygen, a temperature of 400–600°C, and a time of 2–4 hours.

[0022] Because lithium nickel manganese oxide materials are prone to structural oxygen loss during high-temperature sintering, resulting in impurities and a high proportion of disordered (Fd-3m) structures, this invention addresses this by using low-temperature annealing to replenish oxygen, eliminate impurities, and alter the ratio of ordered (P4332 space group) to disordered (Fd-3m) structures. Annealing at excessively high temperatures or for excessively long times fails to eliminate impurities and alter the ordered / disordered structure ratio.

[0023] This invention also provides a lithium nickel manganese oxide cathode material, which is prepared by the above method. This material exhibits high stability and good electrochemical performance.

[0024] As a preferred embodiment, the general chemical formula of the lithium nickel manganese oxide cathode material is LiNi. 0.5 Mn a Al b Ti c F d O 4-d , where 1.5>a≥1.3, 0.1≥b≥0.02, 0.1≥c≥0.02, 0.1≥d≥0.02, and a+b+c=1.5.

[0025] This invention also provides an application of lithium nickel manganese oxide cathode material, which is used in the cathode of lithium-ion batteries. Lithium-ion batteries using this cathode material have high specific capacity and good cycle stability.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) By doping with Al, Ti and F elements and combining with specific preparation processes, the material exhibits an excellent truncated octahedral morphology in its microstructure, reducing surface potential energy and effectively controlling the ratio of ordered (P4332 space group) / disordered (Fd-3m) structures in the material, balancing the contradiction between the capacity and cycle retention rate of the cathode material, and significantly improving the structural stability and electrochemical performance of the material.

[0028] (2) When this electrode material is applied to lithium batteries, it can greatly improve battery capacity and cycle stability. Its reversible specific capacity can reach more than 135mAh / g, and the 1C button battery can still maintain more than 90% of its initial capacity after 100 charge-discharge cycles.

[0029] (3) The preparation method of electrode materials is simple and low in cost, making them suitable for industrial production. Attached Figure Description

[0030] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.

[0031] Figure 1 The image shows the XRD pattern of the lithium nickel manganese oxide cathode material prepared in Example 1.

[0032] Figure 2 This is a SEM image of the lithium nickel manganese oxide cathode material prepared in Example 1.

[0033] Figure 3 The graph shows the 0.1C initial charge-discharge voltage-to-capacity ratio of a lithium-ion battery prepared using the cathode material of Example 1.

[0034] Figure 4 The image shows the 1C charge-discharge specific capacity cycle curve of a lithium-ion battery prepared using the cathode material of Example 1.

[0035] Figure 5 This is a SEM image of the cathode material prepared in Comparative Example 1. Detailed Implementation

[0036] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments and accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0037] Example 1

[0038] A lithium nickel manganese oxide cathode material LiNi 0.5 Mn 1.46 Al 0.02 Ti 0.02 F 0.02 O 3.98 Preparation process:

[0039] A mixture of sodium carbonate (sodium source), nickel hydroxide (nickel source), manganese tetroxide (manganese source), aluminum oxide, titanium dioxide, and lithium fluoride, in a molar ratio of Li, Ni, Mn, Al, Ti, and F of 1.03:0.5:1.46:0.02:0.02:0.02, was weighed and mixed. Pure water was added, resulting in a slurry with a solid content of 60%. The mixture was then ground using a sand mill to a particle size of 400 nm. The ground material was then dried using a spray dryer (with the outlet temperature controlled at 100°C). The dried powder was then calcined in a kiln at 750°C for 20 hours, with air introduced during the calcination process (air flow rate 3 m³ / h). 3 / h) to remove waste gas and promote reaction. After calcination, the temperature is reduced to 400℃ and held for 4 hours to complete the annealing of the material. The annealed material is then pulverized into powder particles with a particle size of 5.0μm using an air jet mill. After sieving and iron removal, the finished product is obtained.

[0040] LiNi prepared by solid-state method 0.5 Mn 1.46 Al 0.02 Ti 0.02 F 0.02 O 3.98 The interface morphology of the finished product was observed under a scanning electron microscope (e.g.) Figure 1 As shown in the SEM image, the material powder consists of small particles of about 5.0 μm in size. These particles have an excellent truncated octahedral morphology and low surface potential energy. When used in battery manufacturing, they exhibit fewer cycling side reactions and excellent performance.

[0041] like Figure 2 The image shows LiNi prepared by the solid-state method. 0.5 Mn 1.46 Al 0.02 Ti 0.02 F 0.02 O 3.98 The XRD pattern of the finished product. The cathode material has a (111) crystal plane characteristic peak at a scanning angle of 18.797°, a (311) crystal plane characteristic peak at a scanning angle of 36.44°, and a (400) crystal plane characteristic peak at a scanning angle of 44.3°. The diffraction angles of the other weak peaks also conform to the space group (P4332) / (Fd-3m). There are no other impurity peaks in the X-ray diffraction pattern, indicating that the cathode material has good crystallinity and a pure phase.

[0042] Battery assembly and testing

[0043] (1) Electrode preparation: The synthesized LiNi 0.5 Mn 1.46 Al 0.02 Ti 0.02 F 0.02 O 3.98The material is mixed with a conductive agent (such as acetylene black) and a binder (such as polyvinylidene fluoride) in a mass ratio of 8:1:1, coated onto an aluminum foil current collector, dried, and then pressed into an electrode sheet.

[0044] (2) Assemble the battery: Assemble the prepared electrode sheet with the lithium metal anode, separator and electrolyte into a CR2032 button battery.

[0045] (3) Electrochemical testing: Charge-discharge testing, cycle life testing, and rate performance testing of the assembled lithium-ion batteries. Figure 3 and Figure 4 ).

[0046] from Figure 3 and Figure 4 As can be seen, the button cell battery has a voltage range of 3V to 4.85V, an initial charge capacity of 149.28mAh / g at 0.1C, an initial discharge capacity of 139.55mAh / g, and a cycle retention rate of 96.6% (50 cycles at 1C).

[0047] Example 2

[0048] Lithium nickel manganese oxide cathode material was prepared using the method described in Example 1, with the following differences: the slurry solid content during grinding was 50%, the grinding particle size was 600 nm; the sintering temperature was 800 °C, the sintering time was 18 h, and the air consumption was 4 m³ / h. 3 / h; annealing temperature is 450℃, annealing time is 3.5h.

[0049] The compositional formula of the lithium nickel manganese oxide cathode material prepared under the conditions of this embodiment is LiNi 0.5 Mn 1.42 Al 0.04 Ti 0.0 4F 0.04 O 3.96 .

[0050] Example 3

[0051] Lithium nickel manganese oxide cathode material was prepared using the method described in Example 1, with the following differences: the slurry solid content during grinding was 40%, the grinding particle size was 800 nm; the sintering temperature was 850 °C, the sintering time was 16 h, and the air consumption was 5 m³ / h. 3 / h; annealing temperature is 500℃, annealing time is 3h.

[0052] The compositional formula of the lithium nickel manganese oxide cathode material prepared under the conditions of this embodiment is LiNi 0.5 Mn 1.38 Al 0.06 Ti 0.0 6F 0.06 O 3.94 .

[0053] Example 4

[0054] Lithium nickel manganese oxide cathode material was prepared using the method described in Example 1, with the following differences: the slurry solid content during grinding was 30%, the grinding particle size was 1000 nm; the sintering temperature was 900 °C, the sintering time was 14 h, and the air consumption was 6 m³ / h. 3 / h; annealing temperature is 550℃, annealing time is 2.5h.

[0055] The compositional formula of the lithium nickel manganese oxide cathode material prepared under the conditions of this embodiment is LiNi 0.5 Mn 1.34 Al 0.08 Ti 0.0 8F 0.08 O 3.92 .

[0056] Example 5

[0057] Lithium nickel manganese oxide cathode material was prepared using the method described in Example 1, with the following differences: the slurry solid content during grinding was 20%, the grinding particle size was 1200 nm; the sintering temperature was 950 °C, the sintering time was 12 h, and the air consumption was 8 m³ / h. 3 / h; annealing temperature is 600℃, annealing time is 2h.

[0058] The compositional formula of the lithium nickel manganese oxide cathode material prepared under the conditions of this embodiment is LiNi 0.5 Mn 1.3 Al 0.1 Ti 0.1 F 0.1 O 3.9 .

[0059] Comparative Example 1

[0060] The lithium nickel manganese oxide cathode material was prepared using the method of Example 1, except that the raw materials did not contain aluminum, titanium, or fluorine sources, i.e., no Al, Ti, or F elements were doped.

[0061] The compositional expression of the cathode material prepared under the comparative conditions is LiNi. 0.5 Mn 1.5 O4, its appearance is as follows Figure 5 As shown, its structure is a standard spinel structure. The spinel of the primary particles has high potential energy, which leads to strong side reactions when used in battery materials, affecting the performance of the battery.

[0062] Comparative Example 2

[0063] The lithium nickel manganese oxide cathode material was prepared using the method of Example 1, except that the raw material did not contain a fluorine source, i.e., no F element doping was performed.

[0064] The compositional expression of the cathode material prepared under the comparative conditions is LiNi. 0.5 Mn 1.46 Al 0.02 Ti 0.02 O4.

[0065] Comparative Example 3

[0066] The lithium nickel manganese oxide cathode material was prepared using the method of Example 1, except that the raw material did not contain a titanium source, i.e., no Ti element was doped.

[0067] The compositional expression of the cathode material prepared under the comparative conditions is LiNi. 0.5 Mn 1.48 Al 0.02 F 0.02 O 3.98 .

[0068] Comparative Example 4

[0069] The lithium nickel manganese oxide cathode material was prepared using the method of Example 1, except that the raw material did not contain an aluminum source, i.e., no Al element was doped.

[0070] The compositional expression of the cathode material prepared under the comparative conditions is LiNi. 0.5 Mn 1.48 Ti 0.02 F 0.02 O 3.98 .

[0071] Comparative Example 5

[0072] The lithium nickel manganese oxide cathode material was prepared using the method of Example 1, except that the raw materials did not contain titanium or fluorine sources, i.e., only Al elements were doped.

[0073] The compositional expression of the cathode material prepared under the comparative conditions is LiNi. 0.5 Mn 1.48 Al 0.02 O4.

[0074] Comparative Example 6

[0075] The method of Example 1 was used to prepare lithium nickel manganese oxide cathode material, except that the raw materials did not contain aluminum or fluorine sources, that is, only Ti element was doped.

[0076] The compositional expression of the cathode material prepared under the comparative conditions is LiNi. 0.5 Mn 1.48 Ti 0.02 O4.

[0077] Comparative Example 7

[0078] The method of Example 1 was used to prepare lithium nickel manganese oxide cathode material, except that the raw materials did not contain aluminum or titanium sources, that is, only F element doping was performed.

[0079] The compositional expression of the cathode material prepared under the comparative conditions is LiNi. 0.5 Mn 1.5 F 0.02 O 3.98 .

[0080] Comparative Example 8

[0081] The lithium nickel manganese oxide cathode material was prepared using the method of Example 1, except that no grinding process was performed.

[0082] The compositional expression of the cathode material prepared under the comparative conditions is LiNi. 0.5 Mn 1.46 Al 0.02 Ti 0.02 F 0.02 O 3.98 .

[0083] Comparative Example 9

[0084] The lithium nickel manganese oxide cathode material was prepared using the method of Example 1, except that no annealing treatment was performed.

[0085] The compositional expression of the cathode material prepared under the comparative conditions is LiNi. 0.5 Mn 1.46 Al 0.02 Ti 0.02 F 0.02 O 3.98 .

[0086] The batteries assembled from the cathode materials of all embodiments and comparative examples were subjected to performance tests, and the results are shown in Table 1.

[0087] Table 1 Battery performance test results

[0088]

[0089]

[0090] As shown in Table 1, the modified high-voltage lithium nickel manganese oxide cathode material provided by this invention exhibits excellent capacity, initial efficiency, and cycle performance, while also meeting other performance requirements. It possesses an initial discharge capacity of 135-140 mAh / g and an initial efficiency of ≥93%, even reaching 96%; the capacity retention after 50 cycles is ≥95%, even reaching 96.6%. Considering that coin cells cannot fully utilize the electrochemical performance of this cathode material, it is expected that when the modified high-voltage lithium nickel manganese oxide cathode material obtained by this invention is applied in full cells, its capacity, initial efficiency, and cycle performance will be further improved.

[0091] A comparison of Examples 1-5 shows that the chemical formula of the modified high-voltage lithium nickel manganese oxide cathode material, the type of raw materials used in its preparation, and the adjustment of parameters during the preparation process can affect the electrochemical performance of the high-voltage lithium nickel manganese oxide cathode material. When the parameters are controlled within a specific range, the electrochemical performance of the high-voltage lithium nickel manganese oxide cathode material can reach the optimal level.

[0092] In addition, the sodium-ion battery cathode material in Comparative Example 1 was not doped with any element, while Comparative Examples 5, 6, and 7 were doped with only one element, and Comparative Examples 2, 3, and 4 were doped with only two elements. The results showed that the capacity, first-efficiency performance, and cycle performance of the high-voltage nickel-manganese lithium oxide battery cathode materials obtained in Comparative Examples 2, 3, 4, 5, and 6 were significantly worse. This indicates that in the technical solution provided by this invention, there is a synergistic effect among the three doping elements, which makes the material exhibit an excellent truncated octahedral morphology in its microstructure, reduces the surface potential energy, and effectively controls the ratio of ordered (P4332 space group) / disordered (Fd-3m) structures in the material, which can significantly improve the capacity, first-efficiency performance, and cycle performance of the high-voltage nickel-manganese lithium oxide battery cathode material.

[0093] Comparative Example 8 did not undergo a sand milling process. This not only fails to ensure the uniformity of the raw material mixing, but also results in poor reactivity of the raw materials, leading to defects in the material structure and a significant decrease in performance, especially a significant decrease in capacity.

[0094] Comparative Example 9 was not annealed, and the resulting high-voltage lithium nickel manganese oxide battery cathode material had large internal stress and distortion, resulting in an unreasonable ratio of ordered (P4332 space group) / disordered (Fd-3m) structure, which ultimately significantly reduced the electrochemical performance of the obtained high-voltage lithium nickel manganese oxide battery cathode material in all aspects.

[0095] In summary, the high-voltage lithium nickel manganese oxide cathode material provided by this invention, through doping with Al, Ti, and F elements and combined with a specific preparation process, exhibits an excellent truncated octahedral morphology in its microstructure, reducing surface potential energy and effectively controlling the ratio of ordered (P4332 space group) to disordered (Fd-3m) structures in the material. This balances the contradiction between the cathode material's capacity and cycle retention rate, significantly improving the material's structural stability and electrochemical performance. Therefore, compared with traditional lithium nickel manganese oxide battery cathode materials, it has significant advantages in capacity, first-time efficiency, and cycle life, and is expected to be widely used in energy storage, power, and other fields.

[0096] The embodiments of the present invention have been described in detail above with reference to the accompanying drawings. However, the present invention is not limited to the above embodiments, and various modifications to these embodiments will be readily apparent to those skilled in the art. The general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the present invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a lithium nickel manganese oxide positive electrode material, characterized in that: Raw materials including a nickel source, a manganese source, a lithium source, an aluminum source, a titanium source and a fluorine source are mixed, wet-ground, dried and pressed into shape to obtain a precursor powder; the precursor powder is sintered and annealed to obtain the product.

2. The method for preparing a lithium nickel manganese oxide positive electrode material according to claim 1, characterized in that: The nickel source, manganese source, lithium source, aluminum source, titanium source and fluorine source are mixed according to the molar ratio of Li:Ni:Mn:Al:Ti:F of (1-1.1):(0.4-0.6):(1.4-1.6):(0.01-0.03):(0.01-0.03):(0.01-0.03).

3. The method for preparing a lithium nickel manganese oxide positive electrode material according to claim 1 or 2, characterized in that: The nickel source includes at least one of nickel carbonate, nickel hydroxide, nickelous oxide, and nickel hydroxide; The manganese source includes manganese tetraoxide and / or manganese dioxide; The lithium source includes lithium carbonate and / or lithium hydroxide; The aluminum source includes aluminum oxide and / or aluminum hydroxide; The titanium source is titanium dioxide; The fluorine source includes aluminum fluoride and / or lithium fluoride.

4. The method for preparing a lithium nickel manganese oxide positive electrode material according to claim 1, characterized in that: The raw materials are ground to a particle size of 400 to 1200 nm.

5. The method for preparing a lithium nickel manganese oxide positive electrode material according to claim 1, characterized in that: The drying temperature is 90-120°C; The pressure of the compression molding is 10-30 MPa.

6. The method for preparing a lithium nickel manganese oxide positive electrode material according to claim 1, characterized in that: The sintering conditions are: atmosphere is air and / or oxygen atmosphere, temperature is 750-950° C., and time is 12-20 hours.

7. A method for preparing a lithium nickel manganese oxide positive electrode material according to claim 1 or 6, characterized in that: The annealing conditions are: atmosphere is air and / or oxygen atmosphere, temperature is 400-600° C., and time is 2-4 hours.

8. A lithium nickel manganese oxide positive electrode material, characterized in that: The method is prepared by any one of claims 1 to 7.

9. A lithium nickel manganese oxide positive electrode material according to claim 8, characterized in that: The chemical composition formula of the lithium nickel manganese oxide positive electrode material is LiNi 0.5 Mn a Al b Ti c F d O 4-d , where 1.5>a≥1.3, 0.1≥b≥0.02, 0.1≥c≥0.02, 0.1≥d≥0.02, a+b+c=1.

5.

10. The use of a lithium nickel manganese oxide positive electrode material according to claim 8 or 9, characterized in that: Used in lithium-ion battery positive electrode.

Citation Information

Cited By

  • Preparation method of high-voltage single-crystal spinel lithium nickel manganese oxide positive electrode material

    CN121407226A